2006
DOI: 10.1163/156856806776923434
|View full text |Cite
|
Sign up to set email alerts
|

Lighting, backlighting and watercolor illusions and the laws of figurality

Abstract: We report some novel 'lighting' and 'backlighting' effects in plane figures similar to those which induce the 'watercolor illusion', that is, figures made with outlines composed of juxtaposed parallel lines varying in brightness and chromatic color. These new effects show 'illumination' as an emergent percept, and show how arrangements of 'dark and light' along the boundaries of various plane figures model the volume and strengthen the illusion of depth. To account for these various effects we propose several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Results showed that color spreading could be observed at all background luminances (Pinna et al, 2001; Pinna and Reeves, 2006). Moreover, the results revealed an important interaction between the contour luminances and the background luminance, which can be more clearly seen in the results of color direction analysis in Figures 6A,B.…”
Section: Resultsmentioning
confidence: 98%
“…Results showed that color spreading could be observed at all background luminances (Pinna et al, 2001; Pinna and Reeves, 2006). Moreover, the results revealed an important interaction between the contour luminances and the background luminance, which can be more clearly seen in the results of color direction analysis in Figures 6A,B.…”
Section: Resultsmentioning
confidence: 98%
“…Given two adjacent contours as in the watercolor illusion, the one with the higher luminance contrast in relation to the surrounding regions is seen as the boundary contours of the object, while the contour with the lower luminance contrast is seen as the color of the figure [12][13][14]. In more general terms, the assignment of the role is due to the relative contrast between the two adjacent contours.…”
Section: J Imaging 2018 4 X For Peer Reviewmentioning
confidence: 99%
“…However, you can still see the contrast with its background. It still looks like a "light square" to us, an instance of Pinna's "water colour illusion" (Pinna, 2008;Pinna, Brellstaff, & Spillmann, 2001;Pinna & Deiana, 2015;Pinna & Reeves, 2006;Pinna, Spillmann, & Werner, 2003). …”
Section: The Whole and Its Parts I: Filling The Blackboardmentioning
confidence: 99%